Characterisation of nutrient profile of quinoa (Chenopodium quinoa), amaranth (Amaranthus caudatus), and purple corn (Zea mays L.) consumed in the North of Argentina: Proximates, minerals and trace elements - Nascimento, Ana Cláudia (2014)
Quinoa, amaranth and purple corn are Andean cereals largely consumed in North of Argentina. Nutrient analysis with the purpose of inclusion in the Argentinean FCDB and e-search EuroFIR has become urgent matter. In this work proximate and mineral profile of Andean cereals cultivated in the North of Argentina were determined and compared with rice. Proximate analysis showed that Andean cereals have similar profile but significantly higher (p < 0.05) than rice. Andean cereals are rich sources of iron, copper, manganese and zinc and better than rice. Phosphorus and magnesium quinoa content could contribute up to 55% of consumers DRI. Andean cereals and rice are poor sources of potassium. To guarantee the interchange of data among users and producers of FCDB component values were obtained in compliance with EuroFIR guidelines for compilation process. Present work provides necessary information to FCDB users who wish to have access to food reference analytical parameters.